Cancer, Health-care Backlogs, and the Cost-of-Living Crisis - Oncology, The Lancet. (The Lancet. Oncology, 2022)
As mounting pressures from several fronts—particularly the COVID-19 pandemic, the conflict in Ukraine, and the consequently exacerbated uncertainty around energy supplies—drive the cost-of-living crisis to alarming new heights, both in the UK and internationally, households are coming under increasing financial strain. The UK Government recently ruled out an emergency budget to tackle the situation, and economists are warning households to ensure that their finances are in the best possible shape to endure rising interest rates, huge surges in energy bills, and the continually rising costs of essential goods. The Food Foundation noted sharp rises in food insecurity across the UK in 2020–21, and the Office for National Statistics also reported increased costs of food, gas and electricity, and fuel between November, 2021, and March, 2022. Many people will be forced to make difficult decisions in the coming months, with vulnerable people disproportionately affected; hundreds of thousands of patients with cancer fall into this category. So what happens when the choice becomes between buying food and heating a home, or between paying rent and travelling for cancer treatments?